Questionnaire: A Tool of Primary Data Collection - Parajuli, Biswo Kallyan (Himalayan Journal of Sociology and Anthropology, 2008)
No abstract availableDOI: http://dx.doi.org/10.3126/hjsa.v1i0.1553Himalayan Journal of Sociology & Anthropology Vol.1 2004 p.51-63